Repetitive cross-polarization contacts via equilibration-re-equilibration of the proton bath: Sensitivity enhancement for NMR of membrane proteins reconstituted in magnetically aligned bicelles - Tang, Wenxing; Nevzorov, Alexander A. (Journal of magnetic resonance (1997), 2011)
[Display omitted] ► Cross-polarization (CP) cannot be fully transferred in a single contact for membrane proteins refolded in bicelles. ► This is due to thermodynamic and quantum mechanical bounds, as well as Hartmann-Hahn mismatches. ► The new REP-CP sequence yields a twofold gain for bicelle-reconstituted proteins as compared to a single CP. ► The gain is achieved by employing the differences between T 1 relaxation times for the high and low spins. Thermodynamic limit of magnetization corresponding to the intact proton bath usually cannot be transferred in a single cross-polarization contact. This is mainly due to the finite ratio between the number densities of the high- and low-gamma nuclei, quantum–mechanical bounds on spin dynamics, and Hartmann–Hahn mismatches due to rf field inhomogeneity. Moreover, for fully hydrated membrane proteins refolded in magnetically oriented bicelles, short spin-lock relaxation times ( T 1 ρ ) and rf heating can further decrease cross polarization efficiency. Here we show that multiple equilibrations-re-equilibrations of the high- and low-spin reservoirs during the preparation period yield an over twofold gain in the magnetization transfer as compared to a single-contact cross polarization (CP), and up to 45% enhancement as compared to the mismatch-optimized CP-MOIST scheme for bicelle-reconstituted membrane proteins. This enhancement is achieved by employing the differences between the spin–lattice relaxation times for the high- and low-gamma spins. The new technique is applicable to systems with short T 1 ρ ’s, and speeds up acquisition of the multidimensional solid-state NMR spectra of oriented membrane proteins for their subsequent structural and dynamic studies.